Trilingual Animated Videos Based on Balinese Fables for Enhancing Elementary Students’ Listening Literacy - Kadek Adrian Surya Indra Wirawan; Ida Bagus Putrayasa; Ni Ketut Desia Tristiantari; I Gusti Ayu Agung Manik Wulandari; Ida Bagus Kade Sudika Puja; Ketut Mita Widiastrini; Putu Ayu Nopitayanti (International Journal of Language and Literature, 2025)
The low level of literacy among elementary school students, particularly in listening skills, remains a significant challenge in education. Conventional text-based learning tends to be less engaging and has not adequately addressed students’ learning needs. Therefore, there is a need for technology-based learning media that not only enhances student engagement but also integrates local cultural values. This study aimed to analyze the effectiveness of trilingual animated videos based on Balinese animal fables in improving elementary students’ listening skills. This research employed a Research and Development (R&D) approach with a one-group pretest-posttest design involving 47 students. Data were collected through listening tests, observations, interviews, and documentation, and were analyzed using the Wilcoxon test and paired sample t-test according to the data characteristics. The findings revealed a significant improvement in students’ listening skills after the implementation of the trilingual animated video compared to conventional learning methods. In addition, students demonstrated increased motivation, participation, and engagement during the learning process. These findings indicate that the integration of digital technology and local wisdom through trilingual animated media can create more contextual and meaningful learning experiences. The implications of this study suggest that culturally based and multilingual learning media can serve as an innovative alternative to enhance language literacy while supporting character development and the preservation of local cultural values from an early age.